Hak Terpidana Setelah Masa Penahanan atas Putusan Pidana Bersyarat - Dizar Al Farizi (Lentera Hukum, 2016)
This research is a normative juridical legal research using a statutory approach and a conceptual approach. The collection of material through the literature study method, with primary and secondary legal materials. Furthermore, the legal material is studied and analyzed by the approaches used in this study to answer legal issues in this study. The results of this study indicate: the reduction of the period of detention is one of the conditions that must be met in a decision when the accused is detained. Failure to fulfill these conditions makes the verdict null and void. The problem that occurs is that in conditional criminal decisions, there is often no mention of a reduction in prison terms. Likewise, decisions are null and void which are not strictly regulated in the existing laws and regulations. Detention is the discretion of law enforcement officers that should not be applied to every suspect or defendant. So that the perpetrators of minor crimes or the losses incurred are small, detention is not always necessary. Even if the detention has been carried out, the judge can issue a verdict according to the period of detention. This is to ensure that the apparatus not only enforces the law but also upholds justice. KEYWORDS: Convict, Detention, Conditional Criminal.